The Effectiveness Of The E-Litigation Trial Process Based On Perma No.1 Of 2019 In Divorce Cases In The Medan Religious Courts - Fatta Arbie Permadi Hasibuan; Fauziah Lubis (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The study aims to evaluate the effectiveness of the divorce case trial process using the E-Litigation system and to identify the factors that hinder and support electronic trials at the Medan Class IA Religious Court. The research method used is non-doctrinal law, focusing on the effectiveness of a law and the factors influencing it. The research instruments include laws, books, journals, and scientific works. Data was obtained from observations at the Medan Class 1A Religious Court, followed by interviews with judges, expert staff operating the e-Litigation application, and admins at the e-Court Corner desk. The problem formulation is: What is the opinion of the panel of judges regarding the effectiveness of e-Litigation according to PERMA No. 1 of 2019 in handling divorce cases? The research results indicate that the effectiveness of the E-Litigation process in divorce cases is very high. It facilitates the parties involved in the dispute, reduces court costs, decreases the backlog of cases, and limits the spread of the Covid-19 outbreak. The E-Litigation system is very effective without compromising the substance of the court process or the rights of the litigants, ensuring that the truth is reached through formalities. Therefore, it can be acknowledged that E-Litigation is an effective trial method.